BIODIESEL SYNTHESIS OF COTTON SEEDS OIL (CEIBA PENTANDRA) BY CHEMICALLY TRANSESTERIFICATION PROCESS AND ION FRAGMENTATION OF METHYL ESTE - Gunawan, Erin Ryantin; Wulandari, Siska Ayu; Yuanita, Emmy; Suhendra, Dedy (Alchemy Jurnal Penelitian Kimia, 2014)
Fossil fuel is Commercial energy sources in many communities where their abundance progressively reduced and the resulting environmental pollution. Biodiesel is one alternative fuel made from vegetable oils are suitable to replace the function of fossil fuels and environmentally friendly. Synthesis of biodiesel from cotton seeds oil was carried out by chemically transesterification process. Composition of methyl esters in biodiesel and was analyzed by GC-MS are methyl palmitate (16.71 %), methyl 8,11- octadecadienoic (46.45 %) and methyl linoleate (4.21 %). The highest biodiesel produced from the conversion of the cotton seeds oil amounted to 93.7 % in weight ratio of oil and methanol (1:1) with the catalyst KOH 1 % (w/w of oil). Chemical properties of biodiesel produced meets the standard SNI 04-7182-2006 include saponification value of 120.167 mg KOH / g, acid value of 0.28 mg KOH / g and iod value 55.84 g iod/100g.